2018
DOI: 10.1097/wnp.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Therapeutic Effect of Responsive Neurostimulation Assessed With Scalp EEG Recording: A Case Report

Abstract: The responsive neurostimulation system (RNS) is the first closed-loop neurostimulator approved as an adjunctive treatment for adults with medically refractory focal epilepsy from no more than two seizure foci. In addition to its therapeutic effect, it provides chronic intracranial EEG recordings, with limited storage capacity. Long-term monitoring with scalp EEG recordings can provide additional information regarding seizure patterns, the efficacy of RNS stimulation in aborting individual seizures, and the net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
2
2
0
1
Order By: Relevance
“…Another case report was notable for 95% of long events (defined as >30 seconds) correlating with ictal patterns on scalp EEG. 12 This is in line with findings from a recent study that showed stereo-EEG events of longer duration (mean 108.6 vs. 49 seconds) were more likely to be seen on scalp EEG. 13 This finding is also consistent with this study where episodes with a longer duration (median 39.73 seconds) had a higher chance to be read on scalp EEG as electrographic seizures.…”
Section: Discussionsupporting
confidence: 91%
“…Another case report was notable for 95% of long events (defined as >30 seconds) correlating with ictal patterns on scalp EEG. 12 This is in line with findings from a recent study that showed stereo-EEG events of longer duration (mean 108.6 vs. 49 seconds) were more likely to be seen on scalp EEG. 13 This finding is also consistent with this study where episodes with a longer duration (median 39.73 seconds) had a higher chance to be read on scalp EEG as electrographic seizures.…”
Section: Discussionsupporting
confidence: 91%
“…RNS devices may stimulate several thousands of times per day, with the vast majority of stimulations unassociated with a behaviorally evident or EEG‐evident seizure. This might be sufficient to provide a long‐term neuromodulatory effect, 63 and would be consistent with the observed increasing benefit over time.…”
Section: Invasive Neurostimulation: Implant Considerationssupporting
confidence: 64%
“…Dies deutet auf eine allmähliche Modulation des epileptischen Netzwerks hin, ähnlich wie bei anderen Neuro stimulationsverfahren. (3) Eine Wirksamkeit auf die Anfallsfrequenz zeigte sich auch bei Patienten mit im EEG sichtbaren Anfallsmus tern, deren Anfälle nicht unterbrochen wurden [87].…”
Section: Responsive Neurostimulation (Rns)unclassified